2009
DOI: 10.1124/dmd.109.029991
|View full text |Cite
|
Sign up to set email alerts
|

Down-Regulation of Liver Drug-Metabolizing Enzymes in a Murine Model of Chronic Renal Failure

Abstract: ABSTRACT:Drug metabolism could be altered in patients with chronic renal failure (CRF). In rats, this phenomenon is related to a decrease in liver cytochrome P450 (P450) and phase II enzymes, particularly N-acetyltransferase 2 (NAT2). This study attempted to determine the effects of CRF on liver P450 isoforms and NAT2 expressions by using a CRF mouse model. Two groups of mice were studied: CRF induced by 3/4 nephrectomy and control. Liver protein expression and mRNA levels of the major P450 isoforms involved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 26 publications
(30 reference statements)
1
18
0
Order By: Relevance
“…This is somewhat higher than the 25-30% bioavailability assessed by semi-simultaneous midazolam dosing in healthy volunteers (SDC Figure S2b), 35,37,38 which may support the hypothesis that patients with ESRD have altered drug metabolism capacity due to reduced expression of CYP3A enzymes. [13][14][15]18,19 A direct inhibitory effect on CYP3A enzymes by the fluctuating degree of uremia was observed in the present study. Therefore, it may be proposed that the likely combination Figure 2 Unbound midazolam fraction at the day before ("dirty") and the day after hemodialysis ("clean").…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…This is somewhat higher than the 25-30% bioavailability assessed by semi-simultaneous midazolam dosing in healthy volunteers (SDC Figure S2b), 35,37,38 which may support the hypothesis that patients with ESRD have altered drug metabolism capacity due to reduced expression of CYP3A enzymes. [13][14][15]18,19 A direct inhibitory effect on CYP3A enzymes by the fluctuating degree of uremia was observed in the present study. Therefore, it may be proposed that the likely combination Figure 2 Unbound midazolam fraction at the day before ("dirty") and the day after hemodialysis ("clean").…”
Section: Discussionsupporting
confidence: 69%
“…1,12 The impact of uremic toxins on protein expression is supported by experimental studies in animal models of renal failure where CYP3A expression was reduced. [13][14][15] Similarly, in renal failure rat models, the expression of P-gp was reduced in the intestine and increased in the liver, whereas OATP expression was reduced in the liver. 16,17 Furthermore, the acute effect of removing uremic toxins with hemodialysis has demonstrated an enhanced expression of CYP3A ex vivo.…”
Section: How Might This Change Clinical Pharma-cology or Translationamentioning
confidence: 97%
“…Microbiota-derived uremic toxins interact with several nonrenal clearance pathways, thereby potentially modifying drug dosing-exposure-response relationships in patients with kidney disease [1417]. In fact, alterations in the functional expression of drug metabolizing enzymes and transporters in kidney disease are well documented [1821], and several microbial toxins are potential mediators [22,23]. The uremic milieu is complicated, containing thousands of compounds including numerous endogenous solutes (e.g., urate, parathyroid hormone, inflammatory cytokines) that are not derived from the microbiota, yet may elicit independent pathophysiological effects.…”
Section: Introductionmentioning
confidence: 99%
“…It is well accepted and intuitive that the clearance of drugs whose elimination mainly depends on renal filtration and/or renal transporters is decreased in CKD and AKI. In addition, an increasing number of in vitro [161][162][163][164][165] and in vivo (in rats [164,166,167] and humans [168,169]) studies published in the last 15 years revealed that CKD and end-stage renal disease (ESRD) may decrease the nonrenal clearance of drugs eliminated by metabolizing enzymes and transporters. These data have been incorporated in a PBPK model of renal impairment in which CYP abundance was reduced by 15-85% depending on CYP isoform and renal disease severity compared with healthy controls [170].…”
Section: Renal Failurementioning
confidence: 99%